Purposeful search of hypoglycemic agents among N-arylcarbamides and N-arylsulfamides of [2-(3-R-1Н-[1,2,4]triazole-5-yl)phenyl]amines - S. V. Kholodnyak; K. P. Shabelnik; S. I. Kovalenko; G. O. Gernova; S. D. Trzhеtsinskiy (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki, 2015)
Aim. Formation of N-arylcarbamides and N-arylsulfamides as result of interaction of 2-(3-R-1Н-[1,2,4]triazole-5-yl)phenyl]amines with electrophilic reagents (arylisocyanates and arylsulfonylchlorides) is described in presented article. The optimal conditions for mentioned reactions have been proposed.